The Effect of Variations of Bagasse Sugarcane Fiber Composition with Plastic/Polypropylene Waste Matrix and Paper Sludge Filler on Acoustic Testing on Composite Panels - Kasih Syirpia; - Hidayati; Yenni Darvina; Riri Jonuarti (PILLAR OF PHYSICS, 2022)
Noise can affect a person's health and comfort. Noise can cause mood disorders, anxiety, and stress. One of the efforts to control noise is the selection of acoustic materials. The utilization of these materials can use as panels that can muffle sound, thereby reducing noise.  In this study, bagasse fiber, polypropylene plastic waste, and paper sludge were used as materials in the manufacturing of composite panels. The method used is the impedance tube method. The greaterzthe sound absorption coefficient, the betterethe material is used as a sound dampening material. In this study, the composition of polypropylene plastic and paper sludge was 40:60, and variations in fiber composition of 0%,1%,2%,3% of the total weight of the composite panel. The bagasse fiber used is a fiber that has been alkalized to a good mechanical interlocking between the fiber and the matrix.Based on the results, the highestasound absorptionrcoefficienteis 0.98 atea frequency of 8000 Hzsfor a 3% fiber composition. The lowest soundeabsorptionrcoefficient is 0.63 at arfrequency of 2000eHz, for a 0% fiber composition. The more fiber composition used in the composite panel, the higher the resulting sound absorption coefficient. More bagasse fibers can increase the pores and thickness of the composite panel so it can absorb the sound that passes through it. The greater the soundaabsorption coefficient, the better the materialeis used as sound material. All sample variations meet the standard requirements as noise materials in buildings, namely 0.15